La evaluación procesal y su rol en el cambio en la educación superior - Manrique Villavicencio, Lileya (2009)
The institutions of higher education introduce changes in curriculum in order to ensure the professional quality that they offer. In this paper, we highlight the role of assessment process that helps control and regulate the implementing and consolidation of curriculum changes. The assessment process provides appropriate information and ongoing curriculum development that reveals the potential ofthis type of assessment to educational quality.